The prevalence of stress, stressors and coping mechanisms and the socio-demographic factors associated among the auto-rickshaw drivers in Bengaluru city, India - Amey Joshi (Journal of Family Medicine and Primary Care, 2021)
Context: Socio-demographic and environmental factors attribute to stress for auto-rickshaw driver leading to compromise of driver and passenger safety. Aims: This study assesses the prevalence and socio-demographic factors associated with stress and identifies the stressors and coping mechanisms in auto-rickshaw drivers. Settings and Design: A cross-sectional study was conducted amongst 140 randomly selected auto-rickshaw drivers in Bengaluru city, India. Methods and Material: Data was collected at a place and time convenient to the study participants using semi-structured pre-tested tool. Stress was assessed using Cohen's Perceived Stress Scale. Statistical Analysis: Data was entered and analyzed using Epi Info™ software. Two sample t/ANOVA tests were used to compare the difference in means and standard deviations (SD) between the sub-groups. P <0.05 was considered statistically significant. Results: Mean age of the auto-rickshaw drivers was 32.8 ± 8.3 years, majority belonged to the 25-30 years age-group. About 55.7%, 40.7% and 28.7% were consuming tobacco products, alcohol and some both, respectively. While the prevalence of self-reported stress was 76.4% (n = 107), 78.6% (n = 110) had stress based on Perceived Stress Scale (PSS) assessment. Mean PSS for participants self-reporting stress was 20.51 ± 5.25 as against 12.36 ± 4.98 who did not (P < 0.001). The mean PSS was 17.55 ± 4.13, 20.65 ± 5.23 and 23 ± 5.12 among those who self-reported having mild-, moderate- and severe-degree stress, respectively (P < 0.001). There was no significant association of any socio-demographic factors with the PSS score. Financial problems (n = 51; 47.7%) was the leading stressor, followed by road traffic (n = 49; 45.8%). Conclusions: Appropriate strategies are needed to address the high level of stress among auto-rickshaw drivers.